Haupt postromantyczny? O czterech prozach i dwóch wierszach - Niewiadomski, Andrzej (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article is devoted to the relationship between Zygmunt Haupt’s prose and the romantic worldview, more precisely to the references to Juliusz Słowacki’s works clearly visible in Haupt’s prose. The issue, which has been previously pointed out by other researchers, required verification by means of close analysis of the specific kind of game that Haupt plays with Słowacki’s texts: Beniowski, Lilla Weneda, the poems Do pastereczki… (To a shepherdess…) and Patrz nad grotą… (Look, above the grotto…), and a fragment of Raptularz (Notebook). Seemingly simple references turn out to be part of a design of making a modern attempt at challenging the incommunicable by means of referring to both Słowacki’s text and his biography, together with an ambiguous, and suspended between repetition and ironic distance, attitude towards the romantic diagnoses of existence. Haupt’s prose, referring to many other traditions as well, presents a Mannerist creative design in which the romantic tradition plays a significant role, yet is not the only point of reference.